Formula instruction in English language writing: learnability, teachability and learner variables / Nor Ashikin Ab Manan - Ab Manan, Nor Ashikin (Universiti Teknologi MARA, Kedah, 2016)
This paper discusses pertinent issues in relation to formula instruction. It is based on a quasi- experimental study which was primarily carried out to ascertain whether incorporating formula instruction into an academic writing class is advantageous in improving the participants’ academic writing performance. Since time allocated for academic writing at university level is often limited to explicitly teach a large collection of formulaic expressions in English language, the paper attempts to address the issues of ‘teachable’ and ‘learnability’ in formula instruction. The paper also highlights the effect of two learner variables namely general English language proficiency level and gender on the participants’ post-test performance. Subsequently, the pattern of formula use among the participants from different proficiency levels was examined and discussed. It was concluded based on the findings that formula instruction is beneficial due to the fact that the experimental group outperformed the control group in the post-test. It was found that the effect of proficiency level on the post-test results is significant but the effect of gender is insignificant. Lower level participants were found to have used more target formulas overall and the formulas used were generally high frequency target formulas. On the other hand, higher level participants had utilized mostly low frequency non-target formulas in their post-test.